Thou Shalt Not Take Sides: Cognition, Logic and the Need for Changing How We Believe - Martins, André C. R. (Frontiers in Physics, 2016)
We believe in many different ways. One very common one is by supporting ideas we like. We label them correct and we act to dismiss doubts about them. We take sides about ideas and theories as if that was the right thing to do. And yet, from a rational point of view, this type of support and belief is not justifiable. The best we can hope when describing the real world, as far as we know today, is to have probabilistic knowledge. In practice, estimating a real probability can be too hard to achieve but that just means we have more uncertainty, not less. There are ideas we defend that define, in our minds, our own identity. And recent experiments have been showing that we stop being able to analyze competently those propositions we hold so dearly. In this paper, I gather the evidence we have about taking sides and present the obvious but unseen conclusion that these facts combined mean that we should actually never believe in anything about the real world, except in a probabilistic way. We must actually never take sides since taking sides compromise our abilities to seek for the most correct description of the world. That means we need to start reformulating the way we debate ideas, from our teaching to our political debates. Here, I will show the logical and experimental basis of this conclusion. I will also show, by presenting new models for the evolution of opinions, that our desire to have something to believe is probably behind the emergence of extremism in debates. And we will see how this problem can even have an impact in the reliability of whole scientific fields. The crisis around p-values is discussed and much better understood under the light of this paper results. Finally, I will debate possible consequences and ideas on how to deal with this problem.